Overexploitation and More Than a Decade of Failed Management Leads to No Recovery of the Galápagos Sea Cucumber Fishery - Ramírez-González, Jorge; Moity, Nicolas; Andrade-Vera, Solange; Reyes, Harry (Frontiers in Marine Science, 2020)
Isostichopus fuscus is the most important sea cucumber species exploited in the Eastern Tropical Pacific. It was the most important fishery in the Galápagos in the early 2000s until overfishing led to its collapse and a 5-year total fishing ban was established (2016 to 2021) to try to recover it. The management of I. fuscus in the Galápagos has always considered the population density as an indicator for decision-making. The objective of this study is to review the density as an indicator of the population status of I. fuscus using a stock-production model incorporating covariates methodology. For the first time, population and fishing parameters (K, r and q), reference points (MSY, BMSY, FMSY and DMSY) and indicators (B/BMSY and F/FMSY) were estimated for I. fuscus. The results indicate that the management measures have not prevented the overexploitation of this species for more than a decade. The goal of the I. fuscus management plan in the Galápagos, i.e. the recovering the fishery in a non-fishing scenario, will not be met by 2030. To accomplish its recovery six recommendations are proposed, including to extend the total ban of the fishery and to change the current management indicators to B/BMSY and F/FMSY. This study evidences that management measures taken with little scientific basis can have a pervasive effect on natural resources.